2012
DOI: 10.22547/ber/4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility In Pakistan Economy

Abstract: Research Question/Issue: This research aims to comprehend the level of corporate social responsibility in Pakistan. The need of the hour is to assess and identify the coverage of the corporations toward its social responsibility. How much each of the elements has its contributions in achieving that level and how we can overcome all of these deficiencies? Research Findings/Insights: By archival data from different companies in Pakistan with a sample of 110 to 120 companies. We find that Pakistan has a moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
(6 reference statements)
0
10
0
2
Order By: Relevance
“…In the context of Pakistan, few studies are available that studied the association of CSR and employees' commitment. For instance, a research conducted by Awan, Kamal, Rafique, and Khan (2012) was aimed at comprehending the level of corporate social responsibility in Pakistan, by identifying the coverage corporations had toward social responsibility. Data from a sample of 110–120 companies in Pakistan were collected for analysis, which showed that Pakistan had a moderate level of corporate social responsibility, with social accountability and investment being the highest contributing variables.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Pakistan, few studies are available that studied the association of CSR and employees' commitment. For instance, a research conducted by Awan, Kamal, Rafique, and Khan (2012) was aimed at comprehending the level of corporate social responsibility in Pakistan, by identifying the coverage corporations had toward social responsibility. Data from a sample of 110–120 companies in Pakistan were collected for analysis, which showed that Pakistan had a moderate level of corporate social responsibility, with social accountability and investment being the highest contributing variables.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CSR has emerged as a vital concept with political, social, and economic dimensions in both developing and developed countries (Carroll, 1999;Jamali & Karam, Pakistan is no exception to the aforementioned context of developing countries. Perhaps, Pakistan became acquainted with CSR for the first time when issue of child labor in the football industry (Sialkot, Pakistan) hit the international headlines (Winstanley, Clark, & Leeson, 2002;Awan, Kamal, Rafique, & Khan, 2012). This epidemic issue gave rise to the emergence of national and international non-governmental organizations (NGOs), specifically those NGOs which were working towards the awareness of CSR (Securities Exchange Commission of Pakistan [SECP], 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Model ini berisi empat dimensi, yakni akuntabilitas dan investasi social, perlindungan dan keberlanjutan lingkungan, tanggung jawab corporate governance dan tanggung jawab ekonomi, etika dan sumber daya manusia (Kanji & Chopra, 2010). Model ini juga digunakan di Pakistan (Awan, Kamal, Rafique, & Khan, 2012). Hasil temuan di Inggris dan Pakistan dengan menggunakan model ini adalah sama.…”
Section: Hipotesis Penelitianunclassified